PHRASEOLOGICAL UNITS WITH ZOONYMIC COMPONENTS IN LINGUISTICS AND TRANSLATION STUDIES - Azimjon Axmedov (International Journal of Literature and Language Studies, 2023)
This article is devoted to the study of phraseological units with zoonym components in Uzbek and English languages. The article analyzes the concept of phraseology, the main features of phraseological units, the linguistic nature of zoonyms, and their role within phraseological units. Furthermore, the specific characteristics of zoonym-based phraseological units - such as imagery, national-cultural specificity, emotional-expressive nature, and metaphorical quality - are revealed. Through a comparative-typological analysis of zoonym phraseological units in Uzbek and English, their semantic groups, similarities, and differences have been identified. The article highlights the linguoculturological significance of zoonym phraseological units and the possibilities of expressing the national mentality, traditions, and worldview of a people through them.